Patient preferences for psychological support in inflammatory arthritis: a multicentre survey. Issue 1 (26th September 2014) - Dures, Emma; Almeida, Celia; Caesley, Judy; Peterson, Alice; Ambler, Nicholas; Morris, Marianne; Pollock, Jon; Hewlett, Sarah
Abstract : Objectives: Inflammatory arthritis (IA) can lead to anxiety, depression, pain and fatigue. Psychological support can improve quality of life and self-management; and European and American guidelines recommend support be offered. This study examined patient views on psychological support for their IA. Methods: A questionnaire designed by researchers, patient partners and clinicians was administered to 2280 patients with IA. Results: 1210 patients responded (53%): 74% women; mean age 59 years (SD 12.7); patient global 5 (2.3); disease duration <5 years (41%), 5–10 (20%), >10 (39%). Only 23% reported routinely being asked about social and emotional issues by a rheumatology professional, but 46% would like the opportunity to discuss psychological impact. If offered, 66% of patients reported they would use a self-management/coping clinic (63% pain management, 60% occupational therapy, 48% peer support groups, 46% patient education, 46% psychology/counselling). Patients want support with managing the impact of pain and fatigue (82%), managing emotions (57%), work and leisure (52%), relationships (37%) and depression (34%). Preferences are for support to be delivered by the rheumatology team (nurse 74%, doctor 55%) and general practitioners (GPs) (51%). Only 6% of patients stated that social and emotional issues were not relevant. Conclusions: Demand for psychological support is high; however, less than a quarter of patients reported being asked about social and emotional issues, suggesting a gap between needs and provision. The preference is for delivery from rheumatology clinicians and GPs, and research should establish whether they have the skills and resources to meet patients' needs.